The Effect of Vaccination Status on Total Lymphocyte Count in Horses Affected by Equine Herpes Virus-1 Myeloencephalopathy - María de la Cuesta-Torrado; Valentina Vitale; Ana Velloso Alvarez; Patricia Neira-Egea; Clairianne Diss; Juan Cuervo-Arango (Animals)
Equine herpesvirus 1-induced myeloencephalopathy has a significant impact on the equine industry. Nevertheless, the clinical variables that may affect the severity of the disease are still under investigation. The objective of this research is studying the relationship between the level of lymphopenia and vaccination status with the severity of the disease in horses at an event, considering whether they had been correctly vaccinated or not prior to exposure to EHV-1. Ten horses were admitted to a veterinary teaching hospital following an equine herpesvirus myeloencephalopathy outbreak during an international show jumping competition in Spain. Data were collected from passport vaccination records, daily analyses, and the clinical histories of the affected horses. Correctly vaccinated horses had a significantly longer hospitalization duration (6/10, 15.5 ± 1.2 days) compared to incorrectly vaccinated horses (4/10, 12.5 ± 1.2 days; p = 0.01). Lymphopenia (<1.6 × 103 lymphocytes/µL) was the most common leukogram abnormality. Correctly vaccinated horses demonstrated a higher lymphocyte count compared to incorrectly vaccinated horses within 24 h of admission (p < 0.01). This difference remained significant from days 1 to 4 and on day 6 post-admission (p =0.03). This study found that lymphopenia is a common leukogram alteration in equine herpesvirus 1-infected horses, and horses correctly vaccinated prior to an equine herpesvirus myeloencephalopathy outbreak tend to have a longer hospitalization time. Correctly vaccinated horses exhibited higher lymphocyte counts during the first 24 h and throughout hospitalization compared to incorrectly vaccinated horses. The immune system could play a relevant role in influencing the severity of equine herpesvirus myeloencephalopathy outbreaks, highlighting the need for further studies in this area.